Artsakh’s Settlements And Infrastructure: Target Of Azerbaijani Aggression During The 2020 War - Avanesyan, Iskuhi (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Once again, made by Azerbaijan, we witnessed crimes during the military operations against Artsakh in 2020. The 44-day war was marked by widespread breaches of international law, deliberate attacks on civilian infrastructure and cultural monuments, the use of prohibited weapons, and other war crimes. This resulted in thousands of casualties, tens of thousands of wounded and displaced individuals, and extensive destruction. During the 44-day war, Azerbaijani armed forces launched systematic and coordinated attacks on nearly all settlements in Artsakh, targeting residential houses, public buildings, and educational institutions. From the very first day of the war, Azerbaijan launched relentless shelling and bombing campaigns on Stepanakert and multiple communities across Askeran, Martuni, Hadrut, Martakert, Karvachar, and Kashatagh districts. Thousands of civilians were left homeless as their apartments and houses were either destroyed or rendered uninhabitable. Throughout the war, more than 170 peaceful settlements were targeted using aircraft, heavy artillery, rockets, and tanks. Throughout the entire 44-day war, Azerbaijan’s military-political leadership, while continuing to commit war crimes, deliberately and periodically targeted key civilian infrastructure across Artsakh, including power, communication, gas and water supply systems, bridges, and food storage facilities. Since September 27, the telephone and Internet network has been another deliberate target. First, Azerbaijani hackers caused serious problems in the communication system for several days, resulting in tens of thousands of civilians being unable to communicate for long periods. Schools, kindergartens, shops and other facilities were also targeted. During the war, the key infrastructure, including roads and bridges, was heavily damaged. Major roads, particularly those connecting Stepanakert with neighboring villages, as well as inter-district and inter-community roads, were targeted. These attacks clearly violated the principle of distinction between civilian and military targets, demonstrating that Azerbaijan's strikes were deliberate and targeted in nature, further confirming the intentionality of the war crimes committed during the September 2020 conflict. Մարդկության և իրավահավասարության դեմ ուղղված հանցագործությունները շարունակում են սպառնալիք մնալ աշխարհի խաղաղությանն ու անվտանգությանը։ Նման հանցագործություններն ի հայտ եկան նաև 2020 թ․ Արցախի դեմ Ադրբեջանի վարած պատերազմական գործո-ղությունների ընթացքում։ 44-օրյա պատերազմը, որն ուղեկցվում էր Ադրբեջանի կողմից միջազգային իրավունքների լայնածավալ խախտումներով, քաղաքացիական ենթակառուցվածքների և մշակութային հուշարձանների միտումնավոր թիրախավորմամբ, արգելված զինատեսակների կիրառմամբ և պատերազմական այլ հանցագործություններով, հանգեցրեց հազարավոր զոհերի և տասնյակ հազարավոր վիրավորների, տեղահանումների և ավերածությունների։ Պատերազմի հետևանքով Արցախի մի շարք շրջաններ ենթարկվեցին էթնիկ զտման, իսկ բնակչությունը դարձավ Ադրբեջանի կողմից իրականացված ռազմական հանցագործությունների և զանգվածային ոճրագործությունների զոհ: Սույն հոդվածը նպատակ ունի վերհանելու 2020 թ․ պատերազմի ժամանակ Ադրբեջանի զինված ուժերի հանցագործությունները՝ Արցախի Հանրապետության բնակավայրերն ու ենթակառուցվածքները նպատակային և կանխամտածված թիրախավորումը։ Կատարված ուսումնասիրությունները վկայում վկայում են, որ մեզ հետաքրքող ժամանակահատվածում տարբեր շրջանների քաղաքացիական կառույցներ, բնակելի թաղամասեր, տներ հայտնաբերելու, թիրախավորելու և ոչնչացնելու, ինչպես նաև խաղաղ բնակչության շրջանում վախի մթնոլորտ ստեղծելու նպատակով Ադրբեջանը կիրառել է ունեցած բոլոր զինատեսակները, այդ թվում արգելված տեսակներ։ Կարելի է պնդել, որ Ադրբեջանի զինված ուժերի միտումնավոր և պարբերաբար հարվածումը քաղաքացիական ենթակառուցվածքների առանցքային օբյեկտներին (էլեկտրականության, կապի, գազի և ջրամատակարարման համակարգեր, կամուրջներ, սննդի պահեստներ և այլն) նպատակ ուներ տասնյակ հազարավոր խաղաղ բնակիչների զրկել կյանքի տարրական պայմաններից և հետագա գոյատևման միջոցներից: Ադրբեջանի ռազմական հանցագործություններն ունեցել են համակարգված բնույթ և դրա հիմքում ընկած է եղել նաև խաղաղ բնակչությանն իրենց տներից պարտադրաբար հեռացնելու որոշում:
Keywords: History; Artsakh